CD38 as an immunotherapeutic target in multiple myeloma. (2nd December 2018) - Bonello, Francesca; D'Agostino, Mattia; Moscvin, Maria; Cerrato, Chiara; Boccadoro, Mario; Gay, Francesca
ABSTRACT: Introduction : Multiple myeloma (MM) is a currently incurable hematologic tumor with heterogeneous clinical behavior and prognosis. During the last years, survival improved due to a better understanding of MM biology and the development of novel drugs, although it still remains unsatisfactory in many cases: new drugs and treatment strategies are needed. CD38 is uniformly expressed at high levels on MM cells and, to a lesser extent, on the surface of normal hematopoietic and non-hematopoietic cells, making this molecule an interesting target for immunotherapeutic approaches. Areas covered : This review discusses the preclinical and clinical experience on different immunotherapeutic agents targeting CD38 in MM. Expert commentary : Monoclonal antibodies (mAbs) targeting CD38 are currently changing the treatment scenario in MM, allowing physicians to reach unprecedented results, especially when anti-CD38 mAbs are used in combination with consolidated MM treatments. Other immunotherapies targeting CD38 – such as conjugated anti-CD38 mAbs, bispecific antibodies stimulating T cells to eliminate CD38+ MM cells, and CD38-specific chimeric antigen receptor T cells – are interesting strategies, currently at earlier developmental stages.